Decision-Making in the Juvenile Justice System in Illinois, Indiana, Michigan, and Ohio, 1999-2000 - Sarri, Rosemary ([Verlag nicht ermittelbar], 2003)
The goals of the juvenile justice system in the United States have always been multiple, beginning with rehabilitation, the primary goal when the juvenile court was established. More recently, policies advocating accountability seem to have predominated over other goals of the court, and concern exists that structured decision-making (SDM) in support of individual accountability has begun to fundamentally change the juvenile justice system. This study examined the use of SDM in state correctional agencies in Illinois, Indiana, Michigan, and Ohio and in juvenile courts in three counties in each of those states. Data were collected in phases from March 1999 to August 2000 during periodic site visits. Probation officers, judges and referees, prosecutors, and defense attorneys were interviewed in each of the 12 courts. Each survey contained a core set of questions eliciting respondents' views of juvenile justice, disposition objectives, and the use and value of SDM. Questions relevant to particular decision-makers were also included. All respondents provided demographic information and information about their job experience in criminal justice and professional training.